Yap/Taz promote the scavenging of extracellular nutrients through macropinocytosis - King, Bryan (Genes Dev, 2020)
The uptake of macromolecules and cellular debris through macropinocytosis has emerged as an important nutrient acquisition strategy of cancer cells. Genetic alterations commonly found in human cancers (e.g. mutations in KRAS or loss of PTEN) have been shown to increase macropinocytosis. To identify additional effectors that enable cell growth dependent on the uptake of extracellular proteins, pancreatic ductal adenocarcinoma (PDA) cells were selected for growth in medium where extracellular albumin was the obligate source of the essential amino acid leucine. Analysis of global changes in chromatin availability and gene expression revealed that PDA cells selected under these conditions exhibited elevated activity of the transcriptional activators Yap/Taz. Knockout of Yap/Taz prevented growth of PDA cells in leucine-deficient medium, but not in complete medium. Furthermore, constitutively active forms of Yap or Taz were sufficient to stimulate macropinocytosis of extracellular protein. In addition to promoting the uptake of plasma proteins, Yap/Taz also promoted the scavenging of apoptotic cell bodies and necrotic debris by PDA cells. The Yap/Taz transcriptional target Axl was found to be essential for cell growth dependent on the uptake of dead cells and cell debris. Together, these studies suggest that the Hippo pathway effectors Yap and Taz are important transcriptional regulators of endocytic nutrient uptake.